Behavior of Rectangular Reinforced-Concrete Columns under Biaxial Cyclic Loading and Variable Axial Loads - Hugo Rodrigues (2016)
The behavior of reinforced-concrete (RC) elements subjected to axial loading variation in conjunction with cyclic biaxial bending is recognized as a very important research topic with a reduced number of experimental results available. Six full-scale RC rectangular columns were tested and analyzed to study the effects of variable axial load on the hysteretic behavior of RC building columns under biaxial horizontal loading. The experimental results are presented and discussed in terms of damage evolution, global hysteretic behavior, stiffness degradation, columns' capacity, and energy dissipation. The global findings revealed the significant effects of the axial load variation on the hysteretic behavior of RC columns. (C) 2015 American Society of Civil Engineers.